2011
DOI: 10.1007/s11240-011-9947-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction and identification of tetraploids using in vitro colchicine treatment of Gerbera jamesonii Bolus cv. Sciella

Abstract: To induce variation through chromosome doubling in Gerbera jamesonii Bolus cv. Sciella, twoweek-old in vitro grown shoots were treated with various concentrations of colchicine (0.01, 0.05, 0.10, 0.50 or 1% w/v) for 2, 4 or 8 h. Treated shoots were then cultured on Murashige and Skoog (MS) medium supplemented with 8.8 lM 6-benzyladenine (BA) and 155 lM adenine sulphate (ADS), and subsequently transferred to fresh MS medium containing 2.85 lM indole-3 acetic acid (IAA) for rooting. When shoots were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
45
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 39 publications
11
45
0
12
Order By: Relevance
“…Similar observations concerning enhancement of cells, stomata, and organs were noted in newly obtained autotetraploids of Zantedeschia (Cohen and Yao 1996), Chaenomeles japonica (Stanys et al 2006), potato (Stupar et al 2007), Nicotiana sp. (Anssour et al 2009), and Gerbera jamesonii (Gantait et al 2011). Zhang et al (2013) reported that naturally occurring triploid genotypes and tetraploid cultivars of Hemerocallis had significantly thicker flower stems and wider leaves similarly as in our tetraploid plants.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Similar observations concerning enhancement of cells, stomata, and organs were noted in newly obtained autotetraploids of Zantedeschia (Cohen and Yao 1996), Chaenomeles japonica (Stanys et al 2006), potato (Stupar et al 2007), Nicotiana sp. (Anssour et al 2009), and Gerbera jamesonii (Gantait et al 2011). Zhang et al (2013) reported that naturally occurring triploid genotypes and tetraploid cultivars of Hemerocallis had significantly thicker flower stems and wider leaves similarly as in our tetraploid plants.…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, the tetraploids flowered in lower percentages. Similar delays in flowering time of a few days were Data of the nuclear DNA content represent mean ± SD of three samples each with two replications noted in autotetraploids of Zizyphus jujube (Gu et al 2005) and Gerbera jamesonii (Gantait et al 2011) and delays of 2 and 3 weeks in Citrullus lanatus (Jaskani et al 2005) and Vicia villosa (Elradi and Unal 2010), respectively. Our observations showed that initial growth of tetraploids was very slow, but during the next season tetraploids were significantly larger than diploids.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The above-mentioned authors also observed that in vitro produced neo-tetraploid shoots are generally shorted and have wider leaves darker colour compared to diploid ones. Shoot regeneration potential from leaves in pear [Gantait et al 2011] and shoot multiplication rate in gerbera [Sun et al 2011] were significantly lower in tetraploids compared to diploids. In gerbera, shoots of tetraploids required longer period to produced roots and the roots were shorter and less numerous compared to those of diploids.…”
Section: Discussionmentioning
confidence: 86%
“…Differences in phenotype and in vitro growth behaviour between diploids and their neotetraploids were reported for several plant species, e.g. watermelon [Compton et al 1993], gerbera [Gantait et al 2011] and pear [Sun et al 2011]. The above-mentioned authors also observed that in vitro produced neo-tetraploid shoots are generally shorted and have wider leaves darker colour compared to diploid ones.…”
Section: Discussionmentioning
confidence: 94%